Strengthening Character Education through Integrative Islamic Education Management: Synchronizing Teacher and Parent Roles - Sriyanto Sriyanto; Suyatno Suyatno; Ishafit Ishafit (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
This study investigates the strengthening of character education through an integrative Islamic education management framework, focusing on the synchronization of teacher and parent roles at SMA Muhammadiyah 3 Yogyakarta. The research aims to explore how managerial integration, from strategic planning to real-time communication, contributes to consistent moral development among students. This qualitative case study utilizes purposive sampling to select 10 key informants: 3 teachers, 3 parents, 3 students, and the School Principal. Data were collected through in-depth interviews, participatory observations of religious activities, and documentation analysis of Lesson Plans (RPP). Data validity was ensured through method triangulation, comparing verbal accounts with physical evidence of school-parent collaboration. The research finds that effective character education is achieved through a structured, synchronized process across three dimensions: Strategic Governance (integrating values into RPP), Human Resource Development (teachers as moral role models), and Parental Partnership (active involvement in Parenting Workshops). Digital communication via WhatsApp serves as a critical real-time feedback loop between school and home. This study contributes to the field of Islamic Education Management by providing an Integrative-Synchronous Model that transforms parents from passive recipients into active educational collaborators. Its novelty lies in the systematic use of digital communication tools to bridge the gap between institutional governance and the reinforcement of domestic character. The primary limitation is the single-case study design, which may limit the generalizability of the findings to different cultural or secular contexts.